The Use of Linguistic jokes in EFL Classroom - Yusuf Al Arief (English Education Department at FKIP Nommensen University, 2023)
Humor is widely recognized as an effective method for promoting language acquisition and enhancing language skills. Using humor in language training can help students feel more at ease, reduce tension, and encourage good emotions, all of which have a favorable effect on their motivation and engagement. In language-learning environments, linguistic jokes are one sort of humor that has not been well investigated. This study uses descriptive qualitative methodologies to investigate the advantages of linguistic jokes in the English as a foreign language (EFL) classroom. Data were gathered for the study from interviews, focus groups, and classroom observations involving EFL students. The results show that language learners gain from using linguistic jokes in EFL classes in several ways, including greater motivation, increased engagement, improved communication skills, and decreased anxiety. The study also emphasizes how humour can improve the learning environment by encouraging greater participation and a sense of belonging among students. The qualitative data show that learners have good attitudes toward using humour in language acquisition, which lends credence to these findings. The study proposes that EFL teachers utilize humour as a teaching method to facilitate language learning and develop language skills. It also finds that including linguistic jokes in EFL classrooms can benefit language learners in various ways.